Students' Directive Speech Acts in Informal Conversation through WhatsApp in the Covid-19 Pandemic Era - Alfiandy Kamal; Irmayana S; Muhammad Taufik; Dahniar Dahniar (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2023)
The use of technology in pandemic time is inevitably, specially the use of communication tool in learning process to avoid physical contact.  This study aims to describe the types directive speech that students used during learning process using WhatsApp video calls in the pandemic time by using Searle’s approach. This study was qualitative research that using utterances as its data taken from students’ conversation then analyzed by using conversation analysis. This study reveals that there were five types of directive speech acts found in the students’ conversation namely question, inviting, prohibiting, requirement, and advisories type. From all of these five types, questioning was the most uttered type of directive speech act of the students.